Midazolam 전투약이 목표농도 조절방식으로 투여되는 Propofol과 Rocuronium 작용 발현에 미치는 영향 - 구의경; Eui Kyoung Goo; 정철희; Cheol Hee Jung; 김환희; Hwan Hee Kim; 소윤미; Yun Mi So; 나효석; Hyo Seok Na; 박희평; Hee Pyoung Park; et al. (Korean journal of anesthesiology, 2009)
Background: This clinical study was designed to evaluate the effect of midazolam as a premedication on the onset of propofol and rocuronium during propofol target-controlled infusion (TCI). Methods: Seventy four patients (ASA class I or II) were randomly allocated to receive either no premedication (control group) or premedication with 0.04 mg/kg intravenous midazolam (midazolam group). Anesthesia was induced and maintained with propofol TCI. Time from propofol injection to loss of consciousness (LOC) and estimated effect concentration at LOC were recorded. After LOC, rocuronium (0.6 mg/kg) was injected. We monitored the degree of neuromuscular blockade by acceleromyography. The following parameters were measured and compared between groups: Time from rocuronium injection to depression of twitch height below 25%, time to maximal depression of twitch height (defined as rocuronium onset time). Results: Systolic blood pressure before induction was lower in midazolam group (125±15 vs 135±20 mmHg), however, there was no difference in blood pressure at LOC between groups (111±16 vs 106±21 mmHg). In midazolam group, time to LOC in propofol TCI was shorter (63±22 vs. 203±118 sec) and estimated effect site concentration of propofol was significantly lower than control group (0.9±0.3 vs. 2.2±0.4 μl/ml). The onset time of rocuronium was not different between groups (120±39 vs. 137±42 sec). Conclusions: Midazolam pretreatment fastens the onset time of propofol and decreases the propofol requirement for LOC. However, it does not influence the onset of rocuronium. (Korean J Anesthesiol 2009;57:434∼7)